2014
DOI: 10.1007/s00167-014-2965-x
|View full text |Cite
|
Sign up to set email alerts
|

Segond fracture in an adult is not pathognomonic for ACL injury

Abstract: The Segond fracture is an avulsion fracture of the lateral tibial plateau and is considered pathognomonic for anterior cruciate ligament (ACL) injury. A case of a Segond fracture occurring with a clinically, radiologically and arthroscopically intact ACL is presented. This was associated with a serious injury to the posterolateral corner requiring surgical reconstruction. Relevant literature is discussed, and the suggestion is made that, whilst an ACL rupture may be the most commonly noted soft tissue componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…We believe that due to the biomechanical differences previously discussed, the injury resulted in no other significant pathology. While the cases cited above relating to pediatric patients suggest that a Segond fracture without associated ACL tear may not be uncommon [3,[7][8][9], completely isolated Segond fractures have not been frequently documented.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We believe that due to the biomechanical differences previously discussed, the injury resulted in no other significant pathology. While the cases cited above relating to pediatric patients suggest that a Segond fracture without associated ACL tear may not be uncommon [3,[7][8][9], completely isolated Segond fractures have not been frequently documented.…”
Section: Discussionmentioning
confidence: 96%
“…Our case raises issues of mechanism of injury as well as differences in the pediatric versus adult pathoanatomy relative to sports injuries of the knee. It is well known that the Segond fracture can occur without an ACL tear [3,7,8]. However, the presence of a lateral capsular sign will invariably be associated with some other injury to the knee [3,[7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…23,29,31 Also, although cadaveric studies have suggested that internal rotation and varus strain might be part of the injury mechanism, the exact forces needed to create the avulsion are largely unknown. 2,6,17,30 Whereas conventional radiographs have been considered the gold standard for describing Segond fractures, other radiological modalities have provided new and additional information on the size and location of the lesion. 13,19 In a study by Flores et al, 13 bony avulsions were quantified on magnetic resonance imaging (MRI).…”
mentioning
confidence: 99%
“…Gottsegen et al [20] and DeLee et al [21] reported the Segond fracture combined to popliteal tendon avulsion and iliotibial band avulsion. Wharton et al [26] published a case report in which the Segond fracture was combined to posterolateral ligament injury without ACL rupture. Furthermore, Ferreira reported an absolute isolated Segond fracture.…”
Section: Injurymentioning
confidence: 99%